The Aggression-Submission-Conventionalism Scale: Testing a New Three Factor Measure of Authoritarianism - Philip T. Dunwoody; Friedrich Funke (Journal of Social and Political Psychology, 2016)
Altemeyer’s (1981) Right-Wing Authoritarianism scale is the most popular authoritarianism measure today. However, the use of a unidimensional scale to measure a three factor construct and an apparent tautology between items and predictive criteria have garnered criticism. Revisions take one of two main approaches: either they simplify the construct to be unidimensional and create new items or they retain Altemeyer’s three factor theory and alter Altemeyer‘s original items to produce a three factor scale. We combine these two approaches by retaining Altemeyer’s three factor theory while creating new items. Our new measure, the Aggression-Submission-Conventionalism (ASC) scale, allows for a test of Altemeyer’s theory divorced of the original items. The ASC scale was designed to maximize discriminant validity while creating less tautological and more politically and religiously neutral items. A total of 649 participants in three convenience samples from the United States completed surveys showing the ASC scale to have good reliability and validity. The ASC scale was found to have similar predictive validity to other three factor scales but superior discriminant validity. Most importantly, we found a clear contribution of all three factors in predicting ethnocentrism, political intolerance, and anti-democratic attitudes. Authoritarian aggression emerged as the most important and consistent predictor with submission and conventionalism effects dependent upon the criterion. The ASC subscales all added unique variance above current unidimensional measures, with aggression consistently adding the most variance. Our findings support Altemeyer’s three factor theory and show that unidimensional measures fail to capture the nuances of our ASC scale.